International Humanitarian Law and Human Rights Education: An Exploration of Differences and Complementarity (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
This article is meant as a small attempt to deal critically with Humanitarian Law within Human Rights Education. After a quick glance at the nature of Humanitarian Law, its relation to Human Rights Education will be discussed and possibilities for linking it to Human Rights Education will be contemplated. The article’s intention is to initialize a discourse which, after further intensive analysis, should contribute to clarifying the relation between Human Rights Education and education in Humanitarian Law.